A Literature Review of the Evidence for the Effectiveness of Experiential Psychotherapies - Ben Mullings (Psychotherapy and Counselling Journal of Australia)
The purpose of this literature review is to review the evidence base for the effectiveness of experiential psychotherapies, conducted in international and Australian settings. A systematic review of internationally published research from the last five years, and Australian research from the last 10 years, was conducted using PsychINFO, Google Scholar, and Web of Science databases. The findings of research studies included in this review have been integrated with the findings of previous meta-reviews on experiential psychotherapies. Five meta-reviews and 14 recent studies met the inclusion criteria. There is a very high standard of evidence for the effectiveness of experiential psychotherapies with depression, medical conditions and unresolved relationship concerns. Experiential therapies are equally efficacious in improving psychological coping compared to other interventions, including Cognitive Behavioural Therapy. The evidence for the effectiveness of experiential psychotherapies with anxiety is weaker, and further research is needed. Experiential therapists need to be willing to participate in research to build the evidence base for this modality.